Low-phosphorus concentrations and important ferric hydroxide scavenging in Archean seawater. Issue 3 (8th February 2023) - Rego, Eric Siciliano; Busigny, Vincent; Lalonde, Stefan V; Rossignol, Camille; Babinski, Marly; Philippot, Pascal
Abstract: The availability of nutrients in seawater, such as dissolved phosphorus (P), is thought to have regulated the evolution and activity of microbial life in Earth's early oceans. Marine concentrations of bioavailable phosphorus spanning the Archean Eon remain a topic of debate, with variable estimates indicating either low (0.04 to 0.13 μM P) or high (10 to 100 μM P) dissolved P in seawater. The large uncertainty on these estimates reflects in part a lack of clear proxy signals recorded in sedimentary rocks. Contrary to some recent views, we show here that iron formations (IFs) are reliable recorders of past phosphorus concentrations and preserved a primary seawater signature. Using measured P and iron (Fe) contents in Neoarchean IF from Carajás (Brazil), we demonstrate for the first time a clear partitioning coefficient relationship in the P-Fe systematics of this IF, which, in combination with experimental and Archean literature data, permits us to constrain Archean seawater to a mean value of 0.063 ± 0.05 μM dissolved phosphorus. Our data set suggests that low-phosphorus conditions prevailed throughout the first half of Earth's history, likely as the result of limited continental emergence and marine P removal by iron oxyhydroxide precipitation, supporting prior suggestions that changes in ancient marine P availability at the end of the Archean modulated marine productivity, and ultimately, the redox state of Earth's early oceans and atmosphere. Classification: Physical Sciences, Earth, Atmospheric and Planetary Sciences